Von Lübeck zu Kaisersaschern. Die Wandlung in Thomas Manns Vorstellung von seiner geistigen Heimat. - Steinby Liisa (Austria, 2022)
Thomas Mann did not produce any regional literature, despite his Buddenbrooks being a Lübeck novel. In the essay Bilse und ich (1906), he explains that Lübeck was used only as a material to which he assigned symbolic meaning for creating a work of art. However, in the essay Lübeck als geistige Lebensform (1926) Mann writes that Lübeck is the growing ground of his entire artistic work. Representing an ethical stance on life, it stands for Lebensbürgerlichkeit, i.e. a commitment to the responsibilities of life. This is in accordance with how Mann, in his Betrachtungen eines Unpolitischen (1918), describes the Germans as being positioned in the “middle ground” where the demands of the intellect, or spirit (Geist), and the unconscious urges of life attain a balance. In Joseph und seine Brüder, rooted intellectually in the epoch of the Weimar Republic, the idea of Lebensbürgerlichkeit can be recognized in a biblical setting. However, in Doctor Faustus (1947), which mirrors the epoch of the Third Reich, it is Kaisersaschern, the protagonist’s (fictional) school town that represents the Germans’ intellectual-spiritual stance on life, which Mann now describes as an “antiquatedness of the soul”. In this “soul”, the irrational forces of life are uncontrollable. In the essay Deutschland und die Deutschen (1945), Mann describes Lübeck by quotations taken from the description of the medieval atmosphere of Kaisersaschern. Lübeck no longer represents the Lebensbürgerlichkeit but has become a representative of what is questionable (“demonic”) in the Germans.